2007
DOI: 10.1152/ajplung.00291.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke-induced blockade of the mitochondrial respiratory chain switches lung epithelial cell apoptosis into necrosis

Abstract: Increased lung cell apoptosis and necrosis occur in patients with chronic obstructive pulmonary disease (COPD). Mitochondria are crucially involved in the regulation of these cell death processes. Cigarette smoke is the main risk factor for development of COPD. We hypothesized that cigarette smoke disturbs mitochondrial function, thereby decreasing the capacity of mitochondria for ATP synthesis, leading to cellular necrosis. This hypothesis was tested in both human bronchial epithelial cells and isolated mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 43 publications
(46 reference statements)
9
100
0
1
Order By: Relevance
“…Higher CSE concentration or longer periods of stimulation with CSE leads to apoptosis or even necrosis, consistent with the results from other researchers [35,36]. Besides treatment factors, cell type [37] is also one factor that can affect cell apoptosis or necrosis when stimulated.…”
Section: Discussionsupporting
confidence: 91%
“…Higher CSE concentration or longer periods of stimulation with CSE leads to apoptosis or even necrosis, consistent with the results from other researchers [35,36]. Besides treatment factors, cell type [37] is also one factor that can affect cell apoptosis or necrosis when stimulated.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our current findings, van der Toorn et al, showed that CSE blocks the mitochondrial respiratory chain and ATP production in lung fibroblasts. 19 Thus, CSE exposure should drive hTERT-BJ1 fibroblasts toward glycolysis and ketogenesis. As predicted, we observed that CSE-treated fibroblasts displayed a significant increase in L-lactate and ketone production.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that muscle mitochondrial function is altered in patients with COPD (31,118,133,164), and that CS induces rapid depolarization of mitochondrial membrane potential in human pulmonary and bronchial epithelial cells with loss of cellular ATP (163,177). As a damage control mechanism, mitophagy may be activated in response to CS exposure.…”
Section: Figmentioning
confidence: 99%